Gadolinium-enhanced inner ear magnetic resonance imaging for evaluation of delayed endolymphatic hydrops, including a bilateral case. (3rd May 2016) - Fukushima, Munehisa; Oya, Ryohei; Akazawa, Hitoshi; Tsuruta, Yukinori; Inohara, Hidenori
Abstract: Conclusion The data suggests that gadolinium-enhanced inner ear MR imaging is useful for diagnosis of delayed endolymphatic hydrops (DEH) because it is independent of inner ear function, and the size of the affected endolymphatic space is clearly enlarged.Objective This study was performed to semi-quantitatively evaluate the endolymphatic space in patients with all types of DEH using gadolinium-enhanced inner ear magnetic resonance (MR) imaging.Patients and methods Seven patients (age range = 21–77 years; five female, two male) with ipsilateral DEH ( n = 5), contralateral DEH ( n = 1), and bilateral DEH ( n = 1). All patients underwent 3T MR imaging 4 h after intravenous injection of gadolinium. Software was used to determine the size of the endolymphatic space. Pure tone audiometry and caloric testing using an electronystagmogram were carried out.Results One side of the endolymphatic space was dominantly extended in patients with ipsilateral DEH, and both sides of the space were extended in patients with contralateral and bilateral DEH. In patients with ipsilateral DEH, the volume ratio of endolymph to vestibule was 2.5–4.3-times that in the unaffected ear. The volume ratio of endolymph to vestibule was nearly equal in patients with contralateral and bilateral DEH.